The Relation Between Fiscal and Current Account Deficits: The Case of Fragile Five - Kayhan, Selim; Bayat, Tayfur; Dejan, Austin; Taşar, İzzet (Asian Journal of Economic Modelling, 2017)
The purpose of this study is to determine the causality between current account deficits and government expenditures for the ‘Fragile Five’ economies by showing the relation in the context of twin divergence and/or the deficit hypotheses. To do this, we employ the asymmetric causality test developed by Hatemi and Roca (2014) and the rolling windows causality test developed by Balcılar et al. (2010). Results obtained from all tests imply that each country has different characteristics and it is hard to classify in the context of twin deficit and/or convergence hypotheses.